The meaning of urban river pollution and sense of place: an ethnographic study of Klang River, Malaysia - Tajuddin, Nor Azlin (2014)
This paper is based on a PhD research, which investigates values, beliefs and practices associated with two polluted rivers in urban settings – the Klang River in Kuala Lumpur, Malaysia, and the Torrens River, South Australia. However, this paper focuses on the findings from the Klang River ethnographic data. Theoretically, the concept of place is central to this paper. Findings suggest that in the urban setting where rivers have increasingly been polluted and modified, and as a consequence whose water is not suitable for direct contact, the visual faculty plays a prominent role in determining the state of the river. From the perspective of everyday users, what constitutes pollution depends significantly on what can and what cannot be seen with naked eyes. In particular, the colour and texture of water, the decline or abundance of aquatic species in the river are some of the common visual experiences described by the locals indicative of pollution. In conclusion, the concept of place is a useful means to understand and analyse the manner in which people comprehend environmental degradation and more specifically river pollution.